Rekonstruksi Kerangka Epistemologis Tafsir Ilmiah Al-Qur'an: Tafsir Ulul Albab dan Penafsiran Ayat-Ayat Kauniyah - Zunaidi Nur; M. Agus Muhtadi Bilhaq (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The rapid advancement of modern science has stimulated renewed discussions on the relationship between the Qur'an and scientific knowledge, leading to the emergence of diverse models of scientific Qur'anic exegesis. Nevertheless, studies examining the epistemological foundations underlying contemporary scientific tafsir remain limited, particularly regarding how revelation, reason, and empirical science are integrated into a coherent interpretive framework. This study aims to reconstruct the epistemological framework of Tafsir Ulul Albab by Agus Mustofa in interpreting ayat kauniyah. Employing a qualitative library research design with content analysis, the study examines the sources of knowledge, interpretive methodology, and validation principles that characterize the exegetical approach of Tafsir Ulul Albab. The findings demonstrate that its epistemology is constructed upon an integrative paradigm that synthesizes revelation (waḥy), rational inquiry ('aql), and contemporary scientific knowledge. Methodologically, the tafsir employs a deductive-confirmatory approach within a partial thematic (mawḍū'ī) and ra'y interpretive model, where Qur'anic descriptions of nature are interpreted through contemporary scientific discoveries while maintaining the primacy of the Qur'anic text. The validity of interpretation is established through correspondence between scriptural meaning and empirically verified scientific evidence, enabling constructive dialogue between religious knowledge and modern science. This study contributes to contemporary Qur'anic studies by conceptualizing Tafsir Ulul Albab as an integrative epistemological model of scientific exegesis that strengthens interdisciplinary engagement between Qur'anic interpretation and scientific inquiry without reducing the authority of revelation.